The Role of Health Literacy Promotion in Epidemic Control Corona 19 - Mostafa Peyvand; Shiva Kargar; Fatemeh Hajizade (Mashhad University of Medical Sciences, 2020)
In late December 2019, a new kind of Coronavirus, called COVID19, was reported from Wuhan, China. By the fast spread of the virus in China and then in all countries, the people around the world have been deeply frightened. The World Health Organization (WHO) has announced the spread of the virus as the main cause of public health emergencies. The fast spread of the virus and lack of vaccine and definite and specific treatment could be addressed as the main reasons that countries are faced with a huge number of infected people and also confronted them with big challenges in different aspects of health, economic, political, and social. Some of these challenges are directly or indirectly related to the health literacy of people and improving it could solve or at least reduce the challenges . In the last years, health literacy has been considered as one of the most important and determinative factors of health. Health literacy has known as a skill for health decision making in the difficult situation of the patients. The health literacy as a social and cognitive skill has different dimensions such as access, appraising, understanding, and performing the obtained health knowledge and information. The ability to comprehend the educational provision in the patients, as a dimension of health literacy, is significantly important .